A prevalência do bullying entre adolescentes e seu impacto social - Lopes, Gustavo Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Bullying is considered a subtype of violence and is characterized by negative actions by one or more individuals in an unequal power relationship. This issue should be broadly discussed in the scientific setting as it may develop sequels that extend into adulthood bringing personality problems and socialization. The objective of this research was to verify the prevalence of bullying in a representative sample of adolescents. The study was of the cross-sectional epidemiological type of school base. The study included adolescents aged 11 to 16 enrolled in the public school system of a medium-sized municipality in northwest São Paulo. Bullying was assessed using the Kidscape questionnaire. Data were analyzed through descriptive and analytical statistical analysis. According to the results, 48.22% of the adolescents participating in the research had already suffered from bullying, and the most prevalent form of bullying was verbal (46.56%), where the majority were boys (65.14%). Conclude a high prevalence of bullying, with predominance in the male sex and verbal bullying, where prevention practices could change these results

O bullying é considerado um subtipo de violência e caracteriza-se por ações negativas de parte de um ou mais indivíduos numa relação desigual de poder. Esta questão deve ser amplamente discutida no cenário científico, pois pode desenvolver sequelas que se estendem na idade adulta trazendo problemas de personalidade e socialização. O objetivo desta pesquisa foi verificar a prevalência do bullying em uma amostra representativa de adolescentes. O estudo foi do tipo epidemiológico transversal de base escolar. Participaram da pesquisa, adolescentes de 11 a 16 anos, matriculados na rede pública de ensino, de um município de médio porte do noroeste paulista. A prática de bullying foi avaliada utilizando o questionário Kidscape. Os dados foram analisados por meio de análise estatística descritiva e analítica. De acordo com os resultados, 48,22% dos adolescentes participantes da pesquisa já tinha sofrido com o bullying, sendo a forma mais prevalente de intimidação sofrida a verbal (46,56%), onde sua maioria era meninos (65,14%). Conclui-se uma alta prevalência do bullying, com predominância no sexo masculino e bullying verbal, onde práticas de prevenção poderiam mudar estes resultados
Keywords: Adolescentes; Qualidade de vida; Bullying; Ortodontia; Má oclusão; Malocclusion